2001
DOI: 10.1034/j.1600-0854.2001.20707.x
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin‐Dependent and Clathrin‐Independent Endocytosis are Differentially Sensitive to Insertion of Poly (Ethylene Glycol)‐Derivatized Cholesterol in the Plasma Membrane

Abstract: We examined the effect of a cholesterol derivative, poly (ethylene glycol) cholesteryl ether on the structure/function of clathrin-coated pits and caveolae. Addition of the compound to cultured cells induced progressive smoothening of the surface. Markedly, when the incorporated amount exceeded 10% equivalent of the surface area, fluid pinocytosis, but not endocytosis of transferrin, became inhibited in K562 cells. In A431 cells, both clathrin-independent fluid phase uptake and the internalization of fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 43 publications
1
50
0
Order By: Relevance
“…Bulkflow endocytosis may be affected not only by local lipid asymmetry across the bilayer, but also by physical forces such as tension and fluidity [84,85]. That clathrin-independent endocytosis is particularly sensitive to such biophysical parameters is supported by its selective inhibition by low concentrations of PEG-cholesterol, whereas impairment of incurvation of clathrincoated pits requires higher concentrations [86,87]. In this respect, interaction of azithromycin with membrane phospholipids is supported by direct in vitro evidence based on equilibrium dialysis with liposomes [88].…”
Section: Discussionmentioning
confidence: 99%
“…Bulkflow endocytosis may be affected not only by local lipid asymmetry across the bilayer, but also by physical forces such as tension and fluidity [84,85]. That clathrin-independent endocytosis is particularly sensitive to such biophysical parameters is supported by its selective inhibition by low concentrations of PEG-cholesterol, whereas impairment of incurvation of clathrincoated pits requires higher concentrations [86,87]. In this respect, interaction of azithromycin with membrane phospholipids is supported by direct in vitro evidence based on equilibrium dialysis with liposomes [88].…”
Section: Discussionmentioning
confidence: 99%
“…Finally it was also demonstrated that reversing lipid asymmetry by adding lipids to the outer leaflet that could not be transported to the inner leaflet opposed fluid phase and clathrin endocytosis triggering the exocytosis of caveolae vesicles from the cytoplasm [12]. This highlighted how the physical properties of the cell membrane are able to oppose specific and active biological processes.…”
Section: Active Trans-membrane Phospholipid Pumping a Force For Vesimentioning
confidence: 99%
“…This highlighted how the physical properties of the cell membrane are able to oppose specific and active biological processes. However, the energy required to impact on specific processes-e.g., pinocytosis versus clathrin-coated pit formation-may differ as it was also demonstrated that the energy required to inhibit clathrin-mediated endocytosis is about 100 times higher than that required to stop pinocytosis [12]. So the same conceptual physics is used but the energy differs.…”
Section: Active Trans-membrane Phospholipid Pumping a Force For Vesimentioning
confidence: 99%
“…Let us assume that the lipid asymmetry is annihilated, endocytosis will stop. Now, if we reverse the lipid asymmetry -i.e., compact more the outer leaflet via the addition of exogenous lipid species compared to the inner leaflet; endocytosis will stop and exocytosis should be promoted [79][80][81]. In cells, not all receptors are displayed on the membrane, some stay within cells in endosomes or vesicles some may even recycle constantly between the membrane and the intracellular vesicles.…”
Section: Enhancing Mddc Vaccination By Adequately Engineering the Celmentioning
confidence: 99%